Antibacterial Activity from Temulawak Extract (Curcuma xanthorrhiza Roxb) on Growth Inhibition of Staphylococcus epidermidis In Vitro - Ni Wayan Mutiara Warmasari; Desak Ketut Ernawati; Agung Wiwiek Indrayani; Ni Wayan Sucindra Dewi; I Made Jawi (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2020)
Background: Infection is one of the main causes of disease in tropical regions like Indonesia. One of them can be caused by bacterial infection of Staphylococcus epidermidis. Staphylococcus epidermidis is an opportunistic bacterium that attacks individuals when the body's immune system is weak. The incidence of bacterial resistance to antibiotics that already exist so that requires an alternative treatment, one of which is the use of temulawak rhizome extract (Curcuma xanthorrhiza Roxb). Temulawak rhizome is one of the spices which is still often used as traditional medicine among Indonesian people. Temulawak rhizome extract is known to have a variety of chemical contents with active compounds in the form of essential oils xanthorrhizol and curcumin which can affect the rate of bacterial growth.Methods: This study aims to determine the antibacterial activity of temulawak rhizome extract on the growth of Staphylococcus epidermidis bacteria in vitro. The method used in this study is the true experimental post test only control group design. Samples were divided into four treatment concentrations such as the extract concentration of 25%, 50%, 75%, and 100% of temulawak rhizome which was tested by agar diffusion method (Kirby-Bauer).Result: The results of the analyze of variant (ANOVA) test showed a significant difference (p = 0,000). The temulawak extract could inhibit bacterial growth with a medium inhibitory response (5-10 mm). Temulawak rhizome extract showed the greatest inhibition at 100% concentration with an average inhibition zone diameter of 9.20 mm.Conclusion : The extract of temulawak rhizome has antibacterial activity. The higher concentration of temulawak rhizome extract (Curcuma xanthorrhiza Roxb), the greater ability to inhibit the growth of Staphylococcus epidermidis bacteria.